Call for Contributions PLAIO#9 (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
PLA Responses to Urgent Social Realities: Access to Education and Work for Refugee, Migrant, Displaced, and Stateless PeopleFrom its origins, PLA has been championed as a significant tool for social change. The next issue of PLAIO focuses on one dimension of this change-maker status: opening up the worlds of education and work for refugees, migrants, displaced, and stateless people.This issue of PLAIO welcomes diverse contributions on ways that work in the PLA arena has been and can be an effective response to the realities of all groups of migrants, with or without official documentation, of asylees, and of immigrants, who are caught without the status and/or the credentials that they need to prosper. Specifically, a gathering of materials focused on efforts to use PLA to recognize the skills, knowledge, competencies, and/or credentials of those who have been politically, economically, and culturally displaced is central to this upcoming issue.We are calling for materials of all kinds: resources that have been created; policies that have been put in place; research that has been done or is ongoing; practices that have been engaged, voices from researchers and those affected by existing policies; organizations and programs that have been established.Some Context:At the heart of PLA (prior learning assessment) work over the last half-century has been the understanding that all institutions and organizations dedicated to education, adult learning, and training, need to provide access to learning for all and to be fair in creating welcoming environments for all learners, including those who might otherwise have been passed over and whose knowledge and skills might remain unrecognized. We have continued to ask ourselves: How can prior learning assessment in its myriad forms offer opportunities to rethink what we mean by “learning,” pushing us to grapple with what people know and what they have gained outside of the conventional classroom setting. We are thus left with a challenge: How and in what way can PLA assist in creating a more inclusive and holistic learning culture, open to all learners and experiences?In this way, PLA has been and will be part of a significant movement for social change that needs to respond to the social-political-cultural circumstances in which we live. Today, broadening such PLA attention needs to include the experiences and the circumstances of refugees, of those without official documentation, of asylees, and of immigrants, who are caught without the status and the credentials that they need to prosper.Instruction for Contributors:Examination of these kinds of pressing global issues will inform our new issue.In addition, PLAIO very much welcomes other writings on the recognition of prior learning that are not directly tied to this issue’s theme. Scholarly articles should be 7,500 words or less. These writings can be research-based, practice-based, or theoretical. Scholarly articles are blind peer-reviewed. Practice articles, literature reviews, and case studies should be between 500 and 1,000 words.All correspondence, including questions and suggestions about contributions to this PLAIO issue, or any ideas about new ways to present research, practice, and/or reflections should be directed to the following:nan.travers@sunyempire.edu, alan.mandell@sunyempire.edu,rdu@cl3.nl, SForseille@tru.ca.All submissions should be submitted as Microsoft Word or Rich Text Format documents at http://plaio.org.All submissions to PLAIO #9 should be received by 1 June 2025.